Qualidade tecnológica de grãos de genótipos de feijão carioca em função do tempo de armazenamento e do ano de cultivo - Arns, Fernanda Daltrozo (2018)
Carioca beans have national preference, being present in the menu of Brazilians from all regions and consumed by people of all social classes. However, storage conditions and the growing environment may lead to a reduction in the technological quality of the beans. The objectives of this work were: (1) to evaluate whether the genotypes of carioca beans differ for the grains technological quality traits; (2) to investigate the correlations between the traits that confer technological quality in carioca beans; (3) to select carioca bean genotypes with commercial grain standard, with clear seed coat and fast cooking during storage refrigerated (3 to 6 ºC and 65 to 70% RH) and obtained in two years of cultivation. A completely randomized design with three replications was used, and the treatments were combined in a factorial scheme, consisting of nine carioca bean genotypes, four storage times (0, 2, 4 and 6 months) and two years of cultivation (2014 and 2015). The following traits were evaluated: mass of 100 grains, length, width, thickness, shape and flatness of grains, color parameters ("L", a* and b*), percentage of water uptake and cooking time. The data were submitted to analysis of variance. Comparison tests of means were applied for the qualitative factors and regression analysis was used for the quantitative factor. The associations between the traits were evaluated by means of the linear correlation of Pearson for each year of cultivation. The multiplicative index was used for the simultaneous selection of characters that confer technological quality of grains. In the analysis of the variance, a significant triple interaction (genotype x storage time x year of cultivation) was observed for the characters mass of 100 grains, length, width, thickness, shape, b* chromaticity, and absorption of water for the grains. The genotypes of carioca beans evaluated presented genetic variability and respond differently as a function of the storage time and the growing environment for the parameters of grain quality. The genotypes C 10-2-4/41, CNFC 11-948, and Pérola have a mass of 100 grains meet the requirements of the consumer market, with grains of mass superior to 25g and this characteristic is maintained for up to six months of storage. The genotype C 10-2-4/41 shows clearer color (L ≥ 55.00) and lower chromaticity a * and b * values, 6.00 and 16.00, respectively. The degree of flattening of the grains, is promising for the indirect selection of fast cooking carioca beans. The multiplicative index proved to be efficient for the simultaneous selection of characters for the identification of genotypes of carrioca beans with technological grain quality. The genotype C10-2-4/41 will be selected by the breeding program as it presents commercial grain pattern, cleaer color, slow darkening and fast cooking, when subjected to storage in a refrigerated environment for six months.